Design and Synthesis of a New Kind of Cavitand: Tetrapyrazolylcalix[4]arenes and Their Supramolecular Assemblies - Jiang, Xuan-Feng; Cui, Yu-Xin; Yu, Shu-Yan (Synlett, 2014)
Two novel calix[4]arene-based tetrapyrazolyl cavitands with different cavity size were synthesized by multistep reactions. In the solid state, one of the cavitands forms an infinite chain by intermolecular hydrogen bonding. The other cavitand undergoes coordination self-assembly with dimetal corners to form a supramolecular cage.
Keywords: cavitands; calixarenes; hydrogen bonding; self-assembly; macrocycles